Criteria for particles to be levitated and to move continuously on traveling-wave electric curtain for dust mitigation on solar panels. (April 2018) - Zhang, Jie; Zhou, Chuande; Tang, Yike; Zheng, Fuzhong; Meng, Minghui; Miao, Chunzheng
Abstract: Dust accumulation on solar panels reduces power-generation efficiency significantly and even shortens service life of an equipment. Traveling-wave electric curtain technique is effective for removing dust on solar panels. The key issue of removing dust by electric curtain is the directional transport of dust. The continuous motion mode (A new motion mode proposed in this paper. In this mode a particle is transported continuously in one direction) is advantageous to directional transport. The criteria for continuous motion mode are derived by analyzing two jointly sufficient conditions: one is referred to as being continuously levitated from the dielectric surface and the other is being transported continuously in one direction. Levitation and movement analyses indicate that a particle in the "true movable area" can be levitated and transported continuously in one direction if particle acceleration complies with certain conditions; otherwise the particle motion will degenerate into reciprocating motion, but afterward the motion will shift to continuous motion if the x -component of velocity increases to a certain amount. Highlights: Continuous motion mode (CMM) is proposed in this paper as a new motion mode. Criteria for particles to be transported in CMM are derived and tested. Particles will be transported in CMM if they comply with certain conditions. Particles will reciprocate if acceleration is smaller than critical acceleration. Low frequency is advantageous to CMM.